Why character education?. (15th October 2017) - Curren, Randall
Abstract : Character education in schools has been high on the UK political agenda for the last few years. The government has invested millions in grants to support character education projects and declared its intention to make Britain a global leader in teaching character and resilience. But the policy has many critics: some question whether schools should be involved in the formation of character at all; others worry that the traits schools are being asked to cultivate are excessively competitive or military. In this pamphlet Randall Curren sets out a robust defence of character education. He welcomes the political support it presently enjoys, but contends that greater clarity about the nature, benefits and acquisition of good character is essential. In particular, he argues that too narrow a focus on traits like perseverance and resilience is a serious mistake: these traits are only virtues when they are part of a wider set of moral and intellectual qualities, and when their exercise is guided by good judgment. Curren offers us a compelling and coherent account of what good character is and how it might be cultivated in schools. He explains why schools must be needs‐supporting environments that provide students with opportunities to engage in rewarding activity, and why cultivating good character implies promoting the 'fundamental British values' of democracy, the rule of law, individual liberty, and mutual respect and tolerance. His groundbreaking pamphlet promises to expand the scope and strengthen the foundations of character education in British schools, and should go a long way towards allaying the fears of its detractors.